FRI0042 Validation of A Multi-Biomarker Disease Activity Score in Rheumatoid Arthritis in Relation to Imaging Inflammation and Damage. (10th June 2014) - Krabbe, S.; Bolce, R.J.; Brahe, C.H.; Døhn, U.M.; Wu, G.; Ejbjerg, B.J.; Hetland, M.L.; Sasso, E.H.; Chernoff, D.; Hansen, M.S.; Knudsen, L.; Hansen, A.; et al.
Abstract : Background: A multi-biomarker disease activity (MBDA) score has been validated as a measure of disease activity in rheumatoid arthritis (RA). Objectives: This study aimed to further validate the MBDA score in relation to "imaging inflammation" (MRI bone marrow edema and synovitis, US power Doppler (PD) score and grey-scale synovitis (GSS)) and "imaging damage" (CT/MRI/US erosions, radiographs) in an investigator-initiated trial (HURRAH trial, NCT00696059 ). Methods: Fifty-two RA patients with active disease despite conventional DMARD therapy were included. All started adalimumab treatment at baseline and continued on methotrexate. MRI, CT, radiographs and US were performed at baseline, week (w)26 and w52. Blood tests were drawn at baseline, w2, 6, 12, 26, 39 and 52 for measurement of 12 serum biomarkers (VCAM-1, EGF, VEGF-A, IL-6, TNF-RI, MMP-1, MMP-3, YKL-40, leptin, resistin, SAA, CRP) used to generate a Vectra® DA algorithm score. Associations between MBDA score, DAS28-CRP and imaging inflammation and damage were evaluated using Spearman's rank correlations (rho). Smallest detectable difference (SDD) was defined as 2 SD of the intrareader difference. Results: Median (IQR) MBDA score was 63 (47-74) at baseline, declined to 48 (35-65) already at w2 and remained at roughly this level at all following visits. Change in MBDA score correlated with change in DAS28 from baseline to w26 (rho=0.71, p<0.001). MBDA score at w26 correlated with MRI synovitis (rho=0.43, p=0.016), MRI bone marrow edema (rho=0.36, p=0.044) and US PD score (rho=0.35, p=0.039), but not US GSS score (rho=0.10, p=0.56). 10 patients (19%) had progressive joint damage above the SDD by one or more imaging modalities from baseline to w52. Two of these 10 patients were in clinical remission (DAS28<2.6), but none were in remission or low disease activity by the MBDA score at w26. The area under the curve (AUC) for the association between MBDA score with change in CT erosion score from baseline to w52 was borderline significant (rho=0.33, p=0.059). No similar trend was observed for AUC of DAS28 (rho=0.15, p=0.42) Baseline MBDA score and change/percent change in MBDA score at w2 or w6 generally did not correlate to change in imaging scores at w26 and w52. However, percent change in MBDA score at w6 correlated to change in MRI synovitis score from baseline to w26 (rho=0.44, p=0.009), and percent change in MBDA score at w2 correlated to change in Sharp/van der Heijde total score from baseline to w26 (rho=0.45, p=0.004). In similar analyses with DAS28 no correlations were found at 0.01 significance level. 15 patients achieved clinical remission (DAS28<2.6) at w26. Inflammation by MRI and/or US was detected in all of these patients; 6 (40%) had a high MBDA score, 7 (47%) had a moderate MBDA score, 0 (0%) had a low MBDA score and only 2 (13%) were categorized as in MBDA remission. Conclusions: This study further validates the MBDA score as a measure of disease activity in RA, as it correlates with imaging measures of inflammation and joint damage. Disclosure of Interest: S. Krabbe: None declared, R. Bolce Shareholder of: Shareholder of Crescendo Bioscience, Employee of: Employee of Crescendo Bioscience, C. Brahe: None declared, U. Døhn: None declared, G. Wu Employee of: Employee of Crescendo Bioscience, B. Ejbjerg: None declared, M. Hetland: None declared, E. Sasso Shareholder of: Shareholder of Crescendo Bioscience, Employee of: Employee of Crescendo Bioscience, D. Chernoff Shareholder of: Shareholder of Crescendo Bioscience, Consultant for: Consultant for Crescendo Bioscience, M. Hansen: None declared, L. Knudsen: None declared, A. Hansen: None declared, O. Madsen: None declared, M. Hasselquist: None declared, J. Møller: None declared, M. Østergaard: None declared DOI: 10.1136/annrheumdis-2014-eular.4460